2014
DOI: 10.1186/1471-2369-15-168
|View full text |Cite
|
Sign up to set email alerts
|

Observational multicenter study to evaluate the prevalence and prognosis of subclinical atheromatosis in a Spanish chronic kidney disease cohort: baseline data from the NEFRONA study

Abstract: BackgroundCardiovascular events (CVE) are more prevalent in chronic kidney disease (CKD) than in general population, being the main cause of morbimortality. Specific risk factors related to CKD have been suggested, because traditional factors do not fully explain this increase in cardiovascular disease rates. However, the role of atheromatosis, its pathogenesis and evolution are still unclear. The potential use of diagnostic tests to detect subclinical atheromatosis has to be determined.MethodsNEFRONA is a pro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
45
1
12

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(64 citation statements)
references
References 50 publications
(42 reference statements)
6
45
1
12
Order By: Relevance
“…Likewise, in our study, the median cIMT and fIMT values linearly increased in relation to the grade of atherosclerosis in the CKD patient population. These findings correlate with the established knowledge that atherosclerosis is a generalized disease involving several segments of the arterial system [14, 15, 41, 42]. …”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Likewise, in our study, the median cIMT and fIMT values linearly increased in relation to the grade of atherosclerosis in the CKD patient population. These findings correlate with the established knowledge that atherosclerosis is a generalized disease involving several segments of the arterial system [14, 15, 41, 42]. …”
Section: Discussionsupporting
confidence: 76%
“…This somewhat contradicts established and previously published results that have reported a correlation between cIMT and degree of atherosclerosis in CABG patients. One possible explanation for this discrepancy would be the fact that prior published data demonstrated a correlation between IMT values and the number and severity of stenoses in the affected coronary arteries, not the histopathologic grade of atherosclerosis in a different set of arteries (in our case the aorta, renal, brachial, and radial arteries) [14, 15, 41, 42]. Another potential explanation would be that cIMT and fIMT values may only correlate with the grade of atherosclerosis in its early or developing stages, while patients with CABG almost always present with advanced atherosclerotic disease.…”
Section: Discussionmentioning
confidence: 75%
“…Recently, baseline data from the National Observatory of Atherosclerosis in Nephrology (NEFRONA) (16) Study have shown that patients in early CKD stages already have a higher prevalence of atheromatous plaques than those without CKD (17,18), and as previously shown, this prevalence is even higher in advanced stages of CKD (19)(20)(21). However, it is uncertain what the velocity of atheromatosis progression in CKD is (22,23), and little is known about the predictors of plaque progression in patients with CKD.…”
Section: Introductionmentioning
confidence: 92%
“…A physical examination was performed, consisting of anthropometric measures, standard vital tests, and ABI measurements as previously described (16). A pathologic ABI was described as #0.9 or $1.4.…”
Section: Clinical Data and Laboratory Examinationsmentioning
confidence: 99%
“…A physical examination was performed, including in anthropometric measures, standard vital tests and ABI measurement as previously described [16]. A pathological ABI was described as 0.9 or !1.4.…”
Section: Clinical and Biochemical Datamentioning
confidence: 99%